Foot trajectories and loading rates in a transfemoral amputee for six different commercial prosthetic knees: An indication of adaptability. (June 2019) - Abouhossein, Alireza; Awad, Mohammed I.; Maqbool, Hafiz F.; Crisp, Carl; Stewart, Todd D.; Messenger, Neil; Richardson, Robert C.; Dehghani-Sanij, Abbas A.; Bradley, David
Highlights: Based upon the mean correlation transient impact (loading rate) and the heel vertical the biomechanical adaptation of the amputee was evident following a short period of prosthetic knees usage. Injury to the amputee's intact side due to higher impact and stress may be possible due to higher vertical and horizontal speed and loading rate. Slow speed may provide prosthetists with the vision of the amputees' progression of adaptation with a newly prescribed prosthetic knee. Amputee's hip angular rotation continued to extend just before the heel contact, in control subjects the hip is momentarily stationary just before the heel contact occurs. Abstract: Background: The relationship between the functional loading rate and heel velocities was assessed in an active unilateral transfemoral amputee (UTFA) for adaptation to six different commercial prosthetic knees. Objective: To Investigate the short-term process of adaptability for UTFA for two types of prosthetic knees were evaluated, based on the correlation between heel vertical velocity and transient loading rate. Methods: The loading rate was calculated from the slope of ground reaction forces (GRF) and the corresponding time. The heel velocities and GRF were obtained by a motion analysis system. Results: Biomechanical adaptation was evident following a short period of prosthetic knee use based upon the mean transient impact (loading rate) and the heel vertical velocity in slow, normal and fast walking. Trend lines of transient impact versus vertical heel velocity for a set of actively controlled variable damping (microprocessor) and mechanically passive prosthetic knees were all negatively correlated, except for an amputated leg during normal pace and healthy leg during fast pace. For an amputee to adapt well to a prescribed prosthesis excellent coordination between the intact and amputated limbs is required to control placement of the amputated leg to achieve a gait comparable to healthy subjects. Conclusion: There are many factors such as the hip, knee flexion/extension and the ankle plantarflexion/dorsiflexion contributing to the control of the transient impact of an amputee during walking. Therefore, for enhanced control of a prosthetic knee, a multifaceted approach is required. This study showed that UTFA adaption to different prosthetic knees in the short term with slower than self-selected speed is completely achievable based on the negative correlation of ground reaction forces versus linear velocity. Reduced speed may provide the prosthetists with the vision of the amputees' progression of adaptation with a newly prescribed prosthetic knee.